Penerapan Data Mining Menggunakan Algoritma C4.5 Dalam Mengukur Tingkat Kepuasan Para Wali Siswa Pada SMK Letris Indonesia 2 - Rengga Herdiansyah; Muhammad Ramdani (CV. Multi Kreasi Media, 2025)
Education is a process aimed at creating a conducive learning environment so that students can reach their full potential. The C4.5 algorithm is a popular decision tree method because it produces classification models that are easy to understand and effective at comparing data with different types of attributes. Education is the effort to prepare students thru orientation activities, teaching and learning activities, assignments, and other educational activities that can influence attitudes and behavior to improve student learning quality. Education involves complex activities, has comprehensive aspects, and is influenced by many variables. The quality of a nation's education is determined by the quality of its educators. Educators must possess qualifications and a level of proficiency that meet national education standards. The school owned is a vocational high school, also known as SMK Letris Indonesia, which initially had a small building on Raya Jombang and gained public trust thanks to the students attending SMK Letris Indonesia. In the first phase, SMK Letris is committed to building a four-story school building with a total of sixteen classrooms and administrative spaces, so that SMK Letris Indonesia 2 has 1434 students with the following core programs: multimedia, network and network technology, accounting, online business and marketing, office automation and governance, and banking. The C4.5 algorithm is a popular decision tree method that helps determine the satisfaction threshold of student guardians based on relevant indicators.